Histopathological study and molecular characterization of Infectious Bronchitis virus circulating in broilers in Basrah governorate, Iraq - N. H. Megdad; W. M. Seger; Y. J. Mohammed (Journal of the Indonesian Tropical Animal Agriculture, 2023)
The poultry industry plays an important role in the food economics and the food industry in both their layer and broiler chicken. Poultry diseases on the other way impact in the poultry industry especially diseases from virus sources since it does not have a specific treatment except for vaccines with routine prevention and control. This study was designed for the assessment of histopathological changes, molecular diagnosis and phylogenetic analyses of the Infectious Bronchitis virus circulating in broilers in Basrah province in the south of Iraq. The tissue samples were (trachea, lung and kidney). One hundred samples were studied with clinical signs and lesions related to IB. The histopathological changes caused by the virus were studied with hematoxylin and eosin stain, and the causative agent Infectious Bronchitis Virus (IBV) was identified using a polymerase chain reaction combined with explaining the phylogenetic analysis. The results of molecular diagnosis and identification showed the twelve Iraqi field strains of IBV were closely related and shared a high identity of 98.44 %- 99.69 % of each other. Variant 2(IS/1494 like) was a predominant genotype of IBV in the present study, and has high similarity with the variant 2(IS/1494) like a strain of IBV circulating in Iran and in the Kurdistan region north of Iraq. The histopathological findings were desquamation of the cilia of the mucosa layer of the trachea, infiltration of inflammatory cells, hyperplasia of goblet cells with thickening of mucosal layer in some areas infiltration of inflammatory exudate within capillaries and Para bronchus, where the microscopic results in kidney were showed interstitial hemorrhage, necrosis of the renal tubular epithelium, infiltration of inflammatory cell. The present results provided useful information on target organs damaged by IBV and the genetic epidemiology of such virus strains circulating in Basrah governorate Iraq during this year that would be helpful to develop a local vaccine.